2022
DOI: 10.1186/s12880-022-00736-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and anatomic variability of the mandibular lingual foramina: a cone-beam CT study

Abstract: Background To evaluate the distribution of lingual foramina (LF) and their correlation with demographic characteristics and mandible width, shape, and bone thickness in Caucasian Italian patients subjected to cone-beam CT (CBCT). Methods CBCTs were reviewed to assess the number of all LF, midline and lateral LF. We also assessed the relationship of the number of lateral LF with gender and mandibular width, shape, and bone thickness using the Chi Sq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Multiple cadaver studies consistently found that 64%-99.7% of individuals had a median lingual foramen [15][16][17][18][19][20][21] . By gross anatomy, the lateral foramen of the tongue contains a branch of the submental artery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple cadaver studies consistently found that 64%-99.7% of individuals had a median lingual foramen [15][16][17][18][19][20][21] . By gross anatomy, the lateral foramen of the tongue contains a branch of the submental artery.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that the distance from the median lingual foramen to the alveolar ridge is 4.73-24.43 mm, and the average distance is 15.49 mm. The diameter range of the lingual foramen is 0.18-1.8 mm [15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…All surgeons and implantologists should not minimize the risk of life-threatening situations resulting from surgical procedures, including dental implant placement in an apparently safe region of the mandible, especially when they know that MLF/MLC frequency is high and complications may occur [ 8 , 25 , 32 ]. Therefore, it is essential to stress the following advice.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 "The lingual foramina host important vascular and neural structures, derived from the floor of mouth, which perforate the cortical bone of the mandible on the lingual side, providing vascular and nerve supply to the mental region". 10 So, when the mandibular surgery damages the mandibular lingual foramen and blood vessels passing through it, it may cause critical bleeding complications. Furthermore, because the anatomical nomenclature of the mandibular lingual foramen has yet to be established, the naming of the mandibular lingual foramen varies between the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that the sources of blood vessels entering the mandible through the lingual foramen are the sublingual and submental arteries 8,9 . “The lingual foramina host important vascular and neural structures, derived from the floor of mouth, which perforate the cortical bone of the mandible on the lingual side, providing vascular and nerve supply to the mental region” 10 . So, when the mandibular surgery damages the mandibular lingual foramen and blood vessels passing through it, it may cause critical bleeding complications.…”
Section: Introductionmentioning
confidence: 99%